PENINGKATAN KETERAMPILAN MENULIS WACANA SEDERHANA DENGAN METODE ALAMIAH DAN GAMBAR SERI ANAK TUNARUNGU - , SUPARKUN (Pendidikan Luar Biasa, 2012)
Abstract; The purpose of this study is to describe the improvement of simple discourse writing skill through a natural method of discourse and picture series on children with hearing impairment of Class III in SDLBN Bugih Pamekasan. The subject of this study was children with hearing impairment of class III that consisted of 4 children. This class action research conducted in three cycles each cycle consisting of two meetings each meeting takes 60 minutes. Methods of data collection using the method of observation and tests, data were analyzed qualitative descriptive. The results showed that the results of student activity on the cycle I got an average score of 4.17 % at the firts meeting then it increased by 5.7 % in the second meeting. In cycle II the average score was 63 % in the firts meeting then increased by 70 % at the second meeting. Cycle III it was 75 % in the first meeting and it increased by 80 % at the second  meeting. Student learning outcomes in the cycle I got an average score of 4.25 % in the first meeting and then it rose by 5.2 % in the second meeting. In cycle II, the learning outcomes of students in average was 65 % in the first meeting and it rose 72.5 % in the second meeting. In the third cycle, it was obtained the average score of 75 % in the first meeting then it increased by 80 % in the second meeting. The data taken during the learning process of skill implemented in simple discourse writing.